Millimeter‐scale genetic gradients and community‐level molecular convergence in a hypersaline microbial mat - Victor Kunin; Jeroen Raes; J Kirk Harris; John R Spear; Jeffrey J Walker; Natalia Ivanova; Christian von Mering; Brad M Bebout; Norman R Pace; Peer Bork; Philip Hugenholtz (Molecular Systems Biology)
Abstract To investigate the extent of genetic stratification in structured microbial communities, we compared the metagenomes of 10 successive layers of a phylogenetically complex hypersaline mat from Guerrero Negro, Mexico. We found pronounced millimeter‐scale genetic gradients that were consistent with the physicochemical profile of the mat. Despite these gradients, all layers displayed near‐identical and acid‐shifted isoelectric point profiles due to a molecular convergence of amino‐acid usage, indicating that hypersalinity enforces an overriding selective pressure on the mat community.